Modeling The Influential Factors Of 8th Grades Student’s Mathematics Achievement In Malaysia By Using Structural Equation Modeling (SEM) - Ahmad Nazim (Institute of Advanced Engineering and Science, 2014)
This research demonstrates the application of Structural Equation Modeling (SEM) method in order to obtain the best fit model for a more efficient and accurate inter-relationship among variables findings and interpretation. For the purpose of this study, secondary data of Trends in International Mathematics and Science Study (TIMSS) was used. The questionnaire were distributed by using two stage stratified cluster sampling technique to 5733 eighth grades students in Malaysia. A Confirmatory Factor Analysis (CFA), Discriminant Validity and Path Analysis had been conducted to obtain the best fit model of SEM. At the end of the study, a best fit model will be obtained for a better accuracy and precision estimation in further analysis.